Gereja dan Penyandang Disabilitas: Urgensi Gereja dalam Melindungi Nilai Hidup Manusia bagi Penyandang Disabilitas - Simamora, Yuniar Mariska (JURNAL DIAKONIA, 2025)
This article aims to examine the role of the church in responding to, protecting, and valuing human life, particularly for individuals with disabilities, to ensure that they are not marginalized in church life. The church has a responsibility to ensure that every member of the congregation, including those with disabilities, is treated equally without discrimination. Therefore, it is essential for the church to take concrete steps in creating a warm and inclusive church environment where all members receive fair and compassionate treatment.In this study, the author employs a qualitative research method by analyzing various sources such as books and journals to understand how the church can contribute to raising awareness of the value of life for individuals with disabilities. The study emphasizes that people with disabilities have the same inherent value as others and deserve to be respected. No member of the congregation should be favored or neglected, as before God, every human being holds equal worth.